Olfactory Dysfunction in Patients With Coronavirus Disease 2019: A Review - Wei, Guoli; Gu, Jialin; Gu, Zhancheng; Du, Cheng; Huang, Xiaofei; Xing, Haiyan; Li, Lingchang; Zhang, Aiping; Hu, Xingxing; Huo, Jiege (Frontiers in Neurology, 2022)
The continuing coronavirus disease 2019 (COVID-19) epidemic is a global crisis with a profound impact on public health worldwide. Among the several neurological symptoms of patients with COVID-19 reported in clinical practice, olfactory dysfunction (OD) is the most common, occurring as the earliest or even the only clinical manifestation in some cases. Increasing research attention has focused on OD, which is currently listed as one of the main diagnostic symptoms of severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) infection. Multiple clinical and fundamental studies on COVID-19-induced OD are underway to clarify the underlying mechanisms. In this review, we provide a summary of the clinical characteristics, mechanisms, evaluation methods, prognosis and treatment options of COVID-19-induced OD, with a view to improving our understanding of COVID-19-induced OD for the purposes of early identification and precise intervention.